Woolwich Massage terhadap Pengeluaran ASI pada Ibu Postpartum - Riskiyani Riskiyani; Fajar Sari Tanberika; Rizka Mardiya; Rifa Yanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the effect of Woolwich massage on breast milk production in postpartum mothers at the Pangkalan Kasai Community Health Center (UPT Puskesmas), Indragiri Hulu Regency. The method used was a quasi-experimental design with a one-group pretest-posttest. The results of bivariate analysis using the Wilcoxon signed-rank test yielded a p-value of 0.008 <0.05 for breast milk production. Woolwich massage provides comfort to postpartum mothers, reduces engorgement, relieves milk blockages, stimulates the release of the hormone oxytocin, and maintains breast milk production. The conclusion is that Woolwich massage has an effect on breast milk production in postpartum mothers at the Pangkalan Kasai Community Health Center (UPT Puskesmas), Indragiri Hulu Regency in 2025. Keywords: Postpartum Mothers, Breast Milk Production, Woolwich Massage